Systems biology design of the microbe toward the bioremediation of cadmium: a review - Jebril, Nadia Mahmoud Tawfiq (International Journal of Psychosocial Rehabilitation, 2020)
The system biology of a cadmium ion removal microbe is an appealing approach for cleaning up the environment. For the bioremediation of cadmium (II) by a microbe, the molecular study is an operative approach for the biological study of adsorbents as contributing to intracellular accumulation. The molecular study demonstrates known gene resistance and molecular designs of new intracellular accumulation using a molecular technique. Cadmium ion removal is the biggest problem for the practice of cadmium ion bioremediation. The latest developments in biology of systems for the bioremediation of cadmium ions are discussed in this paper.